Goffman and social organization : studies in a sociological legacy - Smith, Gregory W. H., 1950- (Routledge studies in social and political thought, 1999)
This collection brings together many of today's leading sociologists to pursue and build upon the diverse aspects of Goffman's legacy and to discuss key topics of his work.